Copper-catalyzed Pummerer type reaction of α-thio aryl/heteroarylacetates: Synthesis of aryl/heteroaryl α-keto esters. Issue 18 (3rd May 2017) - Saha, Pipas; Ray, Sumit Kumar; Singh, Vinod K.
Graphical abstract: Highlights: Pummerer type reaction for the synthesis of the α -keto ester is described. The reaction proceeds through the generation of a thionium ion in situ . The source of oxygen in α -keto ester is confirmed by isotopic-labelling experiment. Abstract: A copper catalyzed Pummerer type reaction of α -thio aryl/heteroarylacetates is described for the first time. This transformation represents a new route to synthesize α -keto esters, which are important intermediates for pharmaceuticals and organic synthesis. The reaction proceeds via in situ generation of a thionium ion that undergoes hydrolysis to furnish α -keto esters in synthetically viable yields (up to 82%).